Implementation of Traditional Games in the Healthy School Movement (GSS) Program to Improve Physical Health at State Elementary School 2 Muara Dua Lhokseumawe City - Mega Pandu Winata; Rambang Muharramsyah (FKIP - Universitas Riau, 2026)
The decline in physical activity among elementary school students has become a growing concern due to sedentary lifestyles and limited movement-based learning activities. In response, the Healthy School Movement Program encourages schools to promote students’ physical health through structured physical activities. This study aims to analyze the implementation of traditional games within the GSS Program to improve students’ physical health at State Elementary School 2 Muara Dua, Lhokseumawe City. A descriptive qualitative case study approach was employed. Data were collected through observations, in-depth interviews, and documentation involving the principal, teachers, and students, and were analyzed thematically using NVivo software. The findings reveal that traditional games such as gobak sodor and engklek effectively enhance students’ physical fitness, endurance, and activity levels. Supporting factors include strong teacher involvement, high student enthusiasm, and the availability of open spaces, while constraints consist of limited facilities, time constraints, and weather conditions. These challenges were addressed through flexible scheduling and adaptive use of school spaces. In conclusion, the integration of traditional games within the GSS Program is an effective and enjoyable strategy for improving physical health while simultaneously fostering character development and social interaction, thereby supporting a holistic healthy school environment rooted in local cultural values.